2020
DOI: 10.1002/cncy.22238
|View full text |Cite
|
Sign up to set email alerts
|

Application of a machine learning algorithm to predict malignancy in thyroid cytopathology

Abstract: BACKGROUND:The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) comprises 6 categories used for the diagnosis of thyroid fine-needle aspiration biopsy (FNAB). Each category has an associated risk of malignancy, which is important in the management of a thyroid nodule. More accurate predictions of malignancy may help to reduce unnecessary surgery. A machine learning algorithm (MLA) was developed to evaluate thyroid FNAB via whole slide images (WSIs) to predict malignancy. METHODS: Files were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 21 publications
(21 reference statements)
0
44
1
1
Order By: Relevance
“…While TBSRTC includes six diagnostic categories on the estimated risk of malignancy (ROM) ( Table 2 ), 15%–30% of TN continues to be classified as indeterminate TN (ITN), most frequently TBSRTC categories III, IV, and V ( 8 ). Recent studies showed excellent consistency between machine learning (ML) models and cytologists in malignancy prediction ( 49 – 51 ), in which the ROM of TBSRTC III determined by the ML model was considerably lower than by manual classification (4.2% vs. 18.8%) ( 51 ). It’s worth noting that morphological and genetic classifications assisted by the AI model are fairly accurate at distinguishing malignancy from benign TN ( 52 54 ) ( Table 3 ).…”
Section: Applications Of Ai In Cytopathological Evaluation From Fnamentioning
confidence: 99%
“…While TBSRTC includes six diagnostic categories on the estimated risk of malignancy (ROM) ( Table 2 ), 15%–30% of TN continues to be classified as indeterminate TN (ITN), most frequently TBSRTC categories III, IV, and V ( 8 ). Recent studies showed excellent consistency between machine learning (ML) models and cytologists in malignancy prediction ( 49 – 51 ), in which the ROM of TBSRTC III determined by the ML model was considerably lower than by manual classification (4.2% vs. 18.8%) ( 51 ). It’s worth noting that morphological and genetic classifications assisted by the AI model are fairly accurate at distinguishing malignancy from benign TN ( 52 54 ) ( Table 3 ).…”
Section: Applications Of Ai In Cytopathological Evaluation From Fnamentioning
confidence: 99%
“…However, most of these studies proved successful only in analyzing binary outcomes: malignant or benign. Many of these have been small studies and have not demonstrated enough strength to be applied to routine clinical work (32,43,44). One study has shown success in distinguishing benign from malignant tumors in the parotid gland (45).…”
Section: Head and Neckmentioning
confidence: 99%
“…Linear and nonlinear machine-learning algorithms showed similar performance for predicting thyroid nodules malignancy using pathological reports as reference standard [ 23 ]. Recently, a machine-learning algorithm has been proposed to predict malignancy in thyroid FNAs via whole slide images reaching a performance comparable to an expert cytopathologist [ 24 ]. With the development of new mathematical models and the inclusion of novel predictors, the performance for predicting the malignancy of thyroid nodules is expected to increase.…”
Section: Introductionmentioning
confidence: 99%